Aldous Huxley: The Political Thought of a Man of Letters. - Maurini, Alessan (Lexington Books (R and L) : Lexington Books, 2016)
Aldous Huxley: The Political Thought of a Man of Letters examines Huxley's political thinking through an analysis of Brave New World, his most successful political manifesto. This book highlights his contributions to contemporary political theory.